Evaluation of an NCAA sponsored online support group for career-ending injured collegiate athletes transitioning out of sports. Issue 3 (2nd September 2018) - Rohrs-Cordes, Kaitlin; Paule-Koba, Amanda L.
ABSTRACT: Forced early retirement due to a career-ending injury is a unique and traumatic life event for an NCAA collegiate athlete. Although the NCAA financially helps some of these athletes, problems still arise due to inadequate recognition of the psychosocial effects of career-ending injuries. There has been little research to evaluate the effectiveness of a common psychosocial intervention for these athletes. The purpose of this qualitative study was to investigate if an NCAA-sponsored online support group would help collegiate athletes with career-ending injuries transition out of college sport. Participants were identified using purposive criterion sampling. Semi-structured interviews were conducted with former Division I NCAA collegiate athletes who experienced a career-ending injury. Implications practitioners could use to help ease these athletes' transition out of sports were identified and a foundation was established for future studies regarding the helpfulness of online support groups for career-ending injured athletes.